2011
DOI: 10.1111/j.1365-2249.2011.04413.x
|View full text |Cite
|
Sign up to set email alerts
|

Colitogenic role of tumour necrosis factor (TNF) receptors in trinitrobenzene sulphonic acid colitis: TNF-R1 ablation does not affect systemic inflammatory response

Abstract: SummaryTumour necrosis factor (TNF)-a plays a critical role in the pathogenesis of T helper type 1-mediated colitis such as Crohn's disease. However, the roles of its two receptors in mediating pathology remain largely unknown. In this study, trinitrobenzene sulphonic acid (TNBS) was used to induce colitis in TNF-receptor single or double knock-out (DKO) BALB/c mice and in wildtype counterparts. TNF-R1 -/-mice had significantly less weight loss, reduced mortality, colon shortening and oedema, colon histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…However, clinical signs, histopathology and inflammatory biomarkers, such as MPO, returned to baseline levels in knockout earlier than in WT mice, suggesting a detrimental role for TNFR1 in the resolution of acute inflammation. In agreement, other studies demonstrated that TNFR1 ablation attenuated tissue damage after trinitrobenzene sulphonic acid (TNBS) induced colitis [35], which was related to control of NF-κB activity [36]. Yet, previous reports demonstrated that TNFR1 or TNFR2 deficiency led to exacerbation of colitis signs compared with WT counterparts [36,37] and that TNFR1-/-strain had more weight loss and increased mortality after TNBS instillation or DSS intake, respectively [37][38][39].…”
Section: Discussionsupporting
confidence: 65%
“…However, clinical signs, histopathology and inflammatory biomarkers, such as MPO, returned to baseline levels in knockout earlier than in WT mice, suggesting a detrimental role for TNFR1 in the resolution of acute inflammation. In agreement, other studies demonstrated that TNFR1 ablation attenuated tissue damage after trinitrobenzene sulphonic acid (TNBS) induced colitis [35], which was related to control of NF-κB activity [36]. Yet, previous reports demonstrated that TNFR1 or TNFR2 deficiency led to exacerbation of colitis signs compared with WT counterparts [36,37] and that TNFR1-/-strain had more weight loss and increased mortality after TNBS instillation or DSS intake, respectively [37][38][39].…”
Section: Discussionsupporting
confidence: 65%
“…There was no difference in TNF-α levels between TNF-α cTg (5.5±1.0 pg/mL) and control (5.0±2.2 pg/mL) mice at 1 month of age. However, at 3 months of age the TNF-α levels increased in TNF-α cTg (14.3±1.9 pg/mL) mice as compared to controls (6.3±1.7 pg/mL) (Figure 5A) although such increased level was within the reported physiological range for TNF-α levels [66]. Nonetheless, we decided to evaluate whether this TNF-α increase deregulates the immune homeostasis.…”
Section: Resultsmentioning
confidence: 79%
“…In contrast, Nakai et al [11] demonstrated that TNF-R1 ablation attenuated tissue damage after TNBS, which was related to reduced NF-κB activity. Our recent study has shown that TNF signaling via TNF-R1or TNF-R2 play a pathogenic role in TNBS-induced colitis [12]. Overall, these studies underline the complexity of TNF bioactivity via TNF-R1 or 2 during the onset and perpetuation of intestinal inflammation, which may be affected by different TNF-R expression patterns and distinct colitis models used.…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, TNF signaling via TNF-R1 or 2 also appears to have distinct effects on different models of experimental colitis. Our previous study demonstrated that deficiency of TNF-R1 or 2 attenuated intestinal damage and improved the symptoms of TNBS-instilled colitis [12]. This may be explained by that different mechanisms are responsible for the initiation and progression of DSS and TNBS-induced experimental colitis respectively [24].…”
Section: Discussionmentioning
confidence: 97%